Relevance of Technical and Vocational Education and Training in the Employability of Computer Science Graduates - Meneses III, Jesus Mercado (FKIP Universitas Lampung, 2023)
Relevance of Technical and Vocational Education and Training in the Employability of Computer Science Graduates. Objectives: A study was conducted to determine the relevance of Technical Education and Skills Development National Certification in relation to the employment/employability of computer science graduates of Eastern Samar State University, Philippines. Methods: A descriptive-correlational design was used and data was analyzed through mean, frequency and percentage distribution. A null hypothesis was tested using Cramer’s V association method to determine if there exist a correlation. Findings: The results showed that most graduates were employed, a significant number were National Certificate II (NC II) competency test passers, and many considered